Handbook of secure care - Dickins, Geoffrey L.; Sugarman, Philip A.; Picchioni, Marco (London : RCPsych Publications, 2015)
In any society a small proportion of people with mental disorder present with behaviour that transgresses norms and violates the rights of others. Yet these people are often vulnerable themselves to violence, abuse or exploitation by others, or may be at risk of neglect or self-harm. There has been a growing realisation that both protection of the public and the personal recovery of these patients must be championed by progressive, specialist clinicians. This book brings together a wealth of wide-ranging views and evidence from diverse perspectives, including academic expertise and viewpoints from clinicians and patients, on how to manage risk in secure care. It covers the full spectrum of people with mental disorder who require secure care across boundaries of age, diagnosis and gender. Written by experienced clinicians and mental health professionals, the book is invaluable to multidisciplinary mental health teams and criminal justice services. General and forensic psychiatrists, service managers and hospital and community psychiatric nurses will find this thorough handbook an essential resource in their daily work.
The evolution of secure and forensic mental healthcare -- Mental disorder and offending -- Clinical risk assessment in secure care -- Risk management in secure care -- Recovery in secure environments -- Personality disorder -- Women's mental health, aggression and offending -- Offenders with intellectual disability in secure services and the criminal justice system -- Secure mental healthcare for young people -- Secure care for people with autism spectrum disorder -- Acquired brain injury, trauma and aggression -- Managing aggression and violence in older people -- Firesetting in secure settings: theory, treatment and management -- Specialist psychological treatment programmes in secure mental healthcare -- Nursing in secure mental healthcare settings -- Prescribing for specialist populations -- Human rights in secure psychiatric care -- Quality assurance and clinical audit in secure psychiatric care -- Psychological support following violent assault and trauma: what works for staff in secure settings?
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: Forensic psychiatry -- Great Britain; Mentally ill offenders -- Care -- Great Britain; Prisoners -- Mental health services -- Great Britain